Comparison of unconventional aero engine architectures - Noppel, F. G. (Cranfield University, 2011)
In the light of global warming, the associated socio economical consequences, and the projected shortage of natural energy resources and ever rising oil prices, this thesis examines the potential for unconventional aero engine architectures to reduce fuel consumption of passenger aircraft. Current aircraft engines are based on the Brayton cycle, where the working fluid successively experiences isentropic compression, isobaric combustion, and isentropic expansion. Deviations from the ideal cycle in real engines occur through component inefficiencies. The maximum achievable thermodynamic efficiency of the Brayton cycle increases hand in hand with its peak cycle temperature. Since the peak cycle temperature is limited by material properties of the turbine, the maximum cycle efficiency of current jet engines is limited by the laws of thermodynamics. Hence, efficiency improvements of jet engines beyond what is possible with conventional turbofan designs are only feasible through unconventional engine architecture. Several technologies enabling unconventional engine architectures for aircraft propulsion have been identified. They include wave rotor, pulse detonation and internal combustion. These technologies are merged with conventional jet engine technology to form hybrid designs. A one dimensional engine performance model was developed to calculate the performance and allow a comparison of the hybrid cycles with a conventional turbofan cycle. Gradient optimisation techniques were applied to the allow comparison of the best possible designs. Results suggest that of the examined cycles, the hybrid internal combustion cycle has the best potential for fuel savings compared to conventional turbofan cycles.